Inducible brown/beige adipocytes in retro-orbital adipose tissues. (July 2019) - Sugiyama, Makoto; Shindo, Daichi; Kanada, Norihisa; Ohzeki, Takahiro; Yoshioka, Kazuki; Funaba, Masayuki; Hashimoto, Osamu
Abstract: Beige adipocytes and brown adipocytes can generate heat by using mitochondrial uncoupling protein 1 (Ucp1), a thermogenic protein. Browning/beiging is the emergence of beige adipocytes in white adipose tissues (WAT) for cold acclimatization. Here we show the existence of brown/beige adipocytes in retro-orbital WAT in mice. Histologically, Ucp1-positive cells with multilocular lipid droplets were abundant in retro-orbital WAT of immature mice; those cells decreased in number with age. However, Ucp1-positive adipocytes with multilocular lipid droplets emerged in retro-orbital WAT in adult mice, due to cold exposure as short as 3 h. Consistent with this observation, the expression level of Ucp1 mRNA was enhanced in tissues upon cold exposure. Furthermore, eye surface temperature remained within a physiological range during cold challenge. RT-qPCR suggested a mixed phenotype of brown and beige adipocytes in retro-orbital WAT. Transmission electron microscopic observation showed multiple lipid droplets and numerous mitochondria with high cristae density in retro-orbital WAT cells from both control and cold-exposed mice. Our results suggest that warming of the orbital cavity by browning/beiging in retro-orbital WAT is a protective mechanism against cold cataract caused by lowered lens temperature. Highlights: Retro-orbital WAT has Ucp1 positive adipocytes in juvenile mice, while the cells decrease in number in adult mice. Consistently, the eye surface temperature was decreased with aging. The Ucp1 positive adipocytes in retro-orbital WAT were inducible by cold exposure. The Ucp1 positive adipocytes exhibited mixed signature of brown/beige adipocytes.